2019
DOI: 10.3389/fphar.2019.00457
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of NPQ/Spexin in Physiology and Pathology

Abstract: Spexin (SPX), also called neuropeptide Q (NPQ), is a novel endogenous neuropeptide. Spexin gene and protein are widely expressed in central nervous system and peripheral tissues in humans, rodents, goldfish, etc. A few of physiological and pathological roles of spexin are gradually emerged recently. This article summarized the roles of spexin in feeding behavior, gastrointestinal motility, obesity, diabetes, energy metabolism, endocrine, mental diseases, and cardiovascular function. Given the broad roles of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 43 publications
3
38
1
2
Order By: Relevance
“…Recent studies demonstrated that spexin was involved in multiple biological and pathological roles [ 7 ]. It was reported that spexin had effects on regulating bile acid synthesis and metabolism [ 8 ], glucose metabolism, and ameliorated insulin resistance [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that spexin was involved in multiple biological and pathological roles [ 7 ]. It was reported that spexin had effects on regulating bile acid synthesis and metabolism [ 8 ], glucose metabolism, and ameliorated insulin resistance [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the very wide distribution of SPX in both the central nervous system and peripheral tissues, it is difficult to indicate which are its main source. However, based on the literature data and the results obtained in this study, we can generally state that the main sources of this peptide are tissues involved in carbohydrate–lipid metabolism and related to the regulation of food intake and energy management, such as the gastrointestinal tract, liver, pancreas, muscles, and others [ 2 , 22 , 23 ]. Moreover, changes in the blood-serum concentration and expression of this peptide indicate the possibility of SPX acting via multiple signaling pathways, both through endocrine action and autocrine/paracrine interactions [ 23 ].…”
Section: Discussionmentioning
confidence: 98%
“…Despite the fact that the research on this peptide is relatively recent, the knowledge about it has systematically increased. Research conducted on many different groups of animals showed a wide expression of this peptide in many different tissues, including fat tissue/adipocytes [ 152 , 153 , 154 , 155 , 156 , 157 , 158 ]. The first study that connected SPX with fat tissue metabolism were experiments performed by Walewski et al in 2014.…”
Section: Spexinmentioning
confidence: 99%